2020
DOI: 10.34198/ejcs.5121.105118
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition of Cu-Zn-Fe Alloy in Hydrochloric Acid Medium by Crude Ethanol Extracts from Roots-Leaves Synergy of Solanum melongena

Abstract: The corrosion inhibition of Cu-Zn-Fe alloy in hydrochloric acid medium by crude ethanol extracts from roots-leaves synergy of Solanum melongena have been studied with chemical methods (mass loss and gasometric methods). At 3.0 grams per litre concentration of the roots-leaves synergy of Solanum melongena, it was observed that a 98.8 % inhibition efficiency was recorded as corrosion rate of alloy was decreasing with inhibitor increase. Temperature evaluation on the inhibitor showed 99.2 > 88.4 > 85.6 % as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…4 and 5a-b. It was observed that the inhibitor presented a single capacity loop for both S275JR -Mild steel and 1100 -Aluminum which is directed towards a single charge transfer [6,[15][16][17]. The sizes of these loops were observed to increases with the rise up to 2500 ppm which is in line with the increased charge transfer values indicating an adsorption of the inhibitor on both surfaces and a reduction of the exposed area (active sites) of the metal [10,15,16].…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 59%
See 2 more Smart Citations
“…4 and 5a-b. It was observed that the inhibitor presented a single capacity loop for both S275JR -Mild steel and 1100 -Aluminum which is directed towards a single charge transfer [6,[15][16][17]. The sizes of these loops were observed to increases with the rise up to 2500 ppm which is in line with the increased charge transfer values indicating an adsorption of the inhibitor on both surfaces and a reduction of the exposed area (active sites) of the metal [10,15,16].…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 59%
“…The values in Table 3 and 4 showed that the inhibition was highly significant at lower temperatures for both metals. This lower inhibition efficiency as recorded following increased temperature is likely to be the effect of temperature agitation on the corrosion inhibition process, consequent upon the loosely bonded inhibitor molecules at the metal interface [6][7][8][9]12]. The inhibition efficiency was found to be increasing following increased inhibitor concentration but decreasing with rise in temperature (Figs 2 and 3).…”
Section: Gasometric Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…Generally, the results showed that stainless steel have the highest resistance to corrosion at the end of the experimental test followed by mild and then galvanized steel in the weight loss experiment. The decreasing trend of the corrosion rate of the galvanized steel with immersion time can be related to the formation of zinc salt of the organic acid which then reduces the concentration of the corroding media from acidic to alkalinity [13], and thus affecting the rate at which most or all of the atoms on the individual metal surfaces are oxidized and consequently damaged [10]. Galvanized steel when in contact with acidic foods is aggressively attacked by the acid species to yield zinc salts of the organic acids present.…”
Section: Weight Loss Measurementmentioning
confidence: 99%
“…Specifically, some corrosive metals can cause cancer after long-time exposure [9]. Consequently, considering the fact that metallic and environmental factors affect corrosion [10], the purpose of this study is to investigate the impacts of tomato, pepper, and onion pulps on various grinding machine components, such as stainless steel, mild steel, and galvanized steel.…”
Section: Introductionmentioning
confidence: 99%